Cognition, Behavior, and Respiratory Function in Amyotrophic Lateral Sclerosis. (17th July 2012) - Strutt, Adriana M.; Palcic, Jennette; Wager, John G.; Titus, Courtney; MacAdam, Claire; Brown, Jeffrey; Scott, Bonnie M.; Harati, Yadollah; Schulz, Paul E.; York, Michele K.
Abstract : Objective . To examine the relationship between respiratory functioning and neuropsychological performance, mood, and frontal-lobe-mediated behaviors in ALS patients. Methods . Forty-four patients with probable or definite ALS (El Escorial criteria) completed comprehensive pulmonary and neuropsychological assessments as part of their baseline neurological evaluation. Based on their full vital respiratory capacity, 24 and 20 patients were classified as having impaired or intact respiration, respectively. Results . Comparable demographic characteristics, neuropsychological performance, and self-reported mood symptoms were found between ALS patients with intact versus impaired respiration. However, more respiratory-impaired patients were reported by their caregivers as having clinically significant impairments in frontal-lobe-mediated behaviors. Nevertheless, declines in behavior were evidenced from pre- to post-ALS symptom onset for both respiratory groups, and exploratory analyses revealed greater executive functioning deficits in patients with bulbar versus limb onset as well as respiratory-impaired patients not receiving pulmonary interventions versus those utilizing such interventions at the time of testing. Conclusions . Results suggest that the respiratory insufficiency of ALS patients may potentially produce irreversible deficits in executive functioning; yet once treated, impairments in more basic cognitive abilities may be less evident.